The Opportunities and Limitations of Livelihood Capitals of an Urban Agricultural Households - Wanichcha Narongchai; Rukchanok Chmnanmak (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2018)
This study aims at investigating the opportunities and limitations of livelihood capitals of an urban agricultural. With the Participatory Action Research method (PAR) via qualitative approach, 14 agricultural households residing and working in Kra-nuan Municipal District in KhonKaen Province were interviewed in-depth and brainstormed. The data was collected from December 2017 to March 2018 and analyzed using Content Analysis approach. The result showed that urban agricultural households lived in a village located in flourish economic municipal district where accessible facilities and services were available, but they still mainly carried on a traditional agricultural occupation. Due to the expansion of the city and rising cost of living, it was necessary for them to improve their production process. They brainstormed to analyze their resources and realized that they had rich natural, physical, and financial capitals of which they could utilize and make their living out. However, human and social capitals were found to obstruct the development of their occupation. In this situation, they teamed up and changed the production process from relying on long-term corps to implementing the integrated farming in which some land was also allocated for short-term corps for additional income. This was regarded as a livelihood strategy with limited chances and capitals.